Quality Culture Design In Building Madrasah Competitiveness At MAN 2 Malang And MBI Amanatul Ummah Mojokerto - Arif Majid, Mohamad; Eko Sujianto, Agus (CV. Inara, 2025)
Building quality Islamic educational institutions to produce competitive graduates is an urgent need today. The quality is derived from a quality culture, so the quality of Islamic educational institutions should be from ‘the Islamic quality culture’ managed by the institutions themselves. The design of a quality culture is worthy of consideration. Since Islam is a perfect religion, if the ‘Spirit of Islam’ is successfully adapted by an educational institution, the institution deserves to be called a true Islamic educational institution. Such kind of institution can answer most of the public demands. This research was conducted at two Islamic education institutions, MAN 2 Malang and MBI Amanatul Ummah Mojokerto. From the qualitative study, it was found that both institutions had implemented the principles and mechanisms of ‘taking the spirit of Islam’ and using it as the design of the institutions’ quality culture. Thus, this resulted in various quality excellences in students, teachers, educational staff, and educational institutions. The design of the quality culture of both institutions followed the principles of: 1) focus on God’s truth, 2) the power of dedication, 3) riyadlah/self-discipline, and 4) commitment to quality. This is the design of a quality culture with the spirit of Islam in Islamic educational institutions, which is able to produce optimal and sustainable quality.